Perbedaan Tingkat Kecemasan dan Facal Image scale (FIS) pada Anak yang Akan Menghadapi Tindakan Pencabutan dan Penumpatan Gigi di Puskesmas Depok Unit III - Fernanda, Reki; Ayun, Quroti; Purwati, Dwi Eni (Journal of Oral Health Care, 2019)
Anxiety was the feeling of being afraid without any reason to be so. FIS was a measurement scale of anxiety levels in children consisting of five lines of facial expression. Anxiety at retraction was caused by the use of sharp objects such as needles. The act of filling when drilling often makes the child very afraid. Whether there was a difference between the anxiety level and the facial image scale (FIS) in children who will face the extraction and filling action. This was an observational study with a cross-sectional survey study. The population of this study was all children receiving services for the extraction and filling treatment. The sample was 60 respondents. The instruments were an anxiety level questionnaire, a measurement sheet with FIS, and a mobile phone camera. Data analysis used the Mann- Whitney test. The level of anxiety in children who will face the filling treatment was in no anxiety criteria with 24 respondents and FIS in children who will face the extraction treatment was the anxious criteria with 26 respondents. Mann- Whitney test results of anxiety level obtained Asymp.Sig 0,545 > 0,05 and FIS value obtained Asymp.Sig 0,321 < 0,05. It can be concluded that there was no significant difference between anxiety levels and FIS in children who will face tooth extraction and filling treatment.